Quantitative 3-D investigation of faulting in deep mining using Mohr–Coulomb criterion and slip weakening law - Yatao Li; Xuehong Gao; Jianwei Yang; Erhu Bai (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract Assessing the risk of fault-slip rockburst is crucial for ensuring the safety of mining operations and effectively mitigating potential disasters. In this study, we propose an integrated 3-D numerical modeling framework combining the virtual fault (VF), 3-D Mohr–Coulomb criterion model (MC), and slip weakening model (SW) to investigate the dynamics of fault failure and coseismic slip induced by mining activities near faults. Our research focuses on the fault stress ratio (k) and how it responds to variables such as fault dip angle (φ), mining distance (D m), fault frictional parameters (μ s, μ d, and D c), and panel length (W m) within a depth-dependent stress field. Our findings demonstrate that the k serves as a critical indicator of fault reactivity, with its sensitivity to φ and D m, significantly heightening the potential for seismic activities. We found that footwall mining, in particular, affects fault stability more than hanging wall mining, often causing greater instability. Additionally, decreases in normal stress due to mining activities are found to be crucial in triggering fault reactivation and coseismic slip. The SW model reveals that k initially decreases with increasing slip and stabilizes as slip progresses, highlighting the critical role of evolving frictional properties in fault stability. Additionally, this study confirms that mining-induced fault slips exhibit self-similar behaviors analogous to natural faulting, with a proportional relationship between slip distribution and static stress drop, validated through robust numerical analysis. This study enhances the understanding of fault mechanics in mining-induced conditions and provides a robust framework for assessing seismic risks, offering practical insights for improving safety and stability in deep mining operations.